Making transparent environmental management decisions : Applications of the ecosystem management decision support system - Hessburg, Paul F.; Bourgeron, Patrick S.; Reynolds, Keith M. (Environmental Science and Engineering, 2014)
Since 1997, the Ecosystem Management Decision Support (EMDS) system has been used around the world to support environmental analysis and planning in many different application areas, and it has been applied over a wide range of geographic scales, from forest stands to entire countries. An extensive sampling of this diversity of applications is presented in section 2, in which EMDS application developers describe the varied uses of the system. These accounts, together with the requisite background in section 1, provide valuable practical insights into how the system can be applied in the general domain of environmental management.